2014
DOI: 10.12968/bjcn.2014.19.12.578
|View full text |Cite
|
Sign up to set email alerts
|

Living with companion animals after stroke: experiences of older people in community and primary care nursing

Abstract: Living with companion animals after stroke: experiences of older people in community and primary care nursing.Johansson, Maria; Ahlström, Gerd; Jönsson, Ann-Cathrin Ahlström, G., & Jönsson, A-C. (2014). Living with companion animals after stroke: experiences of older people in community and primary care nursing. British Journal of Community Nursing, 19(12), 578-584. DOI: 10.12968/bjcn.2014.19.12.578 General rights Copyright and moral rights for the publications made accessible in the public portal are ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
(32 reference statements)
0
21
0
1
Order By: Relevance
“…Positive psychological outcomes such as increased feelings of wellbeing, self-efficacy, happiness, cheerfulness and relaxation were reported in almost half the studies reviewed (N = 27; 43.5%), as well as a decrease in depressive symptoms, anxiety and stress levels (Enders-Slegers, 2000; Hecht et al , 2001; Suthers-McCabe, 2001; Becker and Morton, 2002; Likourezos et al , 2002; VanZile, 2004; Mallia, 2006; Motooka et al , 2006; Tatschl et al , 2006; Chur-Hansen et al , 2008; de Guzman et al , 2009; Hargrave, 2011; Culbertson, 2013; Gretebeck et al , 2013; Himsworth and Rock, 2013; Putney, 2013, 2014; Johansson et al , 2014; McNicholas, 2014; Bennett et al , 2015; Mayo Clinic, 2015; Zane, 2015; Branson et al , 2016; Yang et al , 2017). Pets could also decrease the stress associated with grief following the loss of a loved one (Wells and Rodi, 2000; Suthers-McCabe, 2001; Dice, 2002; Hara, 2007; Culbertson, 2013; Putney, 2013; McNicholas, 2014; Anderson et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Positive psychological outcomes such as increased feelings of wellbeing, self-efficacy, happiness, cheerfulness and relaxation were reported in almost half the studies reviewed (N = 27; 43.5%), as well as a decrease in depressive symptoms, anxiety and stress levels (Enders-Slegers, 2000; Hecht et al , 2001; Suthers-McCabe, 2001; Becker and Morton, 2002; Likourezos et al , 2002; VanZile, 2004; Mallia, 2006; Motooka et al , 2006; Tatschl et al , 2006; Chur-Hansen et al , 2008; de Guzman et al , 2009; Hargrave, 2011; Culbertson, 2013; Gretebeck et al , 2013; Himsworth and Rock, 2013; Putney, 2013, 2014; Johansson et al , 2014; McNicholas, 2014; Bennett et al , 2015; Mayo Clinic, 2015; Zane, 2015; Branson et al , 2016; Yang et al , 2017). Pets could also decrease the stress associated with grief following the loss of a loved one (Wells and Rodi, 2000; Suthers-McCabe, 2001; Dice, 2002; Hara, 2007; Culbertson, 2013; Putney, 2013; McNicholas, 2014; Anderson et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…They mostly included comparisons of pet owners and non-owners, and did not involve random assignment to conditions, due to the nature of PO and the practical and ethical challenges with randomly assigning PO. Two additional studies classified as level 5 involved interviews of small groups of older adults regarding PO (Johansson et al, 2014), and a focus group of older adult dog walkers (Knight & Edwards, 2008).…”
Section: Physical Health and Exercisementioning
confidence: 99%
“…Similarly, PO was associated with improved survival and lower risk of fatal cardiovascular events in a sample of hypertensive older adults (Chowhurdy et al, 2017). In an additional level 5 study with a small sample size (Johansson et al, 2014), older adults experienced companion animals as important physical and psychosocial contributors to recovery after a stroke. PO was also associated with several other positive physical health and activity outcomes.…”
Section: Physical Health and Exercisementioning
confidence: 99%
“…As an early contribution that adopted such an approach, a Canadian study by Raina, Waltner-Toews, Bonnett, Woodward, & Abernathy (1999) produced longitudinal evidence that pets may support both physical function and psychological well-being for older adults as they age. Other studies have also suggested that pets may support both the mental and physical health of community-dwelling older adults who are managing chronic diseases like type 2 diabetes (Peel, Douglas, Parry, & Lawton, 2010), as well as those recovering from a stroke (Johansson, Ahlström, & Jönsson, 2014) or cardiovascular events (Chowdhury et al, 2017; Friedmann, Thomas, & Son, 2011).…”
Section: Introductionmentioning
confidence: 99%